Mini-laparotomy for repair of infrarenal abdominal aortic aneurysm - Laohapensang K. (2014)
Aim. In this study, we evaluated the surgical results of minimal incision aortic surgery (MIAS) compared with the transabdominal approach (TPA) and the retroperitoneal approach (RPA) to repair non-ruptured infrarenal abdominal aortic aneurysm (AAA). Methods. Three different surgical techniques were studied prospectively in 72 consecutive patients with non-ruptured infrarenal AAA. These patients were randomized into 3 groups of 24 patients each. Group I comprised of patients who underwent MIAS repair. They were compared with group II patients, who underwent the traditionally long midline TPA, and group III patients, who underwent the left RPA to repair non-ruptured infrarenal AAA. All surgery was performed between January 2000 and December 2004. Demographic characteristics, including age, sex, body weight, aneurysm size, previous abdominal operations and comorbid factors of the three groups studied, were compared using the Fischer's exact test. Parameters including operative time, intraoperative fluid administration, and transfusion requirements were compared using the 2-tailed Student t test. Length of stay in the Intensive Care Unit (ICU), time to resumption of regular dietary feeding, and hospital length of stay were recorded and compared using the Wilcox rank sum test. The incidence of 30 day postoperative complications and mortality were compared between the three groups. All 72 patients who entered this study had informed consent. Results. There was no significant difference between group I (MIAS), group II (TPA), and group III (RPA) with regard to age, sex distribution, aneurysm size, or body weight. There was male sex prevalence in all three groups. Surgical exposure of the common femoral arteries was more commonly required in group III (RPA) than in the other groups. Although the length of incision tended to be longer in group III (RPA) than in group II (TPA) and I (MIAS), there was no significant difference in intraoperative time, or aortic cross-clamped time among the three groups. There was a significant difference in the need for intraoperative fluid, the most being in group II (TPA) and the least in group I (MIAS). There was significantly less blood loss in group I (MIAS), as compared with the other 2 groups, but intraoperative blood transfusion for all groups was not significantly different. ICU stay, return to general dietary feeding, and hospital length of stay for group I (MIAS) and III (RPA) were significantly lower than in group II (TPA), which had a higher incidence of postoperative ileus. Conclusion. MIAS is as safe as retroperitoneal repair and standard transabdominal repair in the treatment of non-ruptured infrarenal AAA, and also more cost-efficient than retroperitoneal and standard transabdominal repair.